(untitled) (Cadernos de Sociomuseologia, 2022)
Youth programmes are nowadays central to the education programmes of many international museums, in particular contemporary art museums in North America and the United Kingdom. In line with the specific characteristics of these age group, as an independent audience, these programmes can be grouped in three main types – one-off, short-term and long-term initiatives. The variation of their temporality is grounded on specific goals and strategies that aim to offer young people different ways to access and participate in museums, defining what is called a tier-based programme. Looking into Portuguese museums, the investment on youth, beyond formal education, is a recent but growing phenomenon. Based on the analysis of the youth programmes of five cultural institutions in Lisbon: the Museum of Art, Architecture and Technology (MAAT), BoCA – Biennial of Contemporary Art, Casa da Cerca – Contemporary Art Centre, the Municipal Galleries and LU.CA – Luís de Camões Theater, this paper discusses the potential of an interinstitutional tier-based youth programme. Palavras-chave: jovens; participação; programação cultural; educação artística